The power of beliefs : how strengthening seven core beliefs predicts greater success and a better life - Achor, Shawn (Crown Currency, 2026)
The greatest predictor of your future is the beliefs you hold about the world. In this extraordinary book, world-renowned researcher and author Shawn Achor illuminates how beliefs change the math about what is possible and probable in our lives. And by changing the math, beliefs change our path. Drawing on two decades of research, as well as his work with NASA, the NFL, and over a third of the Fortune 100 companies, Shawn has discovered that the predictive power of beliefs has increased significantly. Beliefs about ourselves, money, the world, politics, faith, and work do more than shape the lens through which we see the world. They shape what happens next. Scientifically speaking, beliefs don't just reflect reality. Beliefs bend reality. Shawn explores the six main ways of changing your and others' beliefs using research-based strategies he has tested everywhere from Wall Street to impoverished schools in Africa, from Camp Pendleton to Camp David. The Power of Beliefs shows how seven core beliefs predict your present, bend the probability of future success, and, in the modern world, are the key to creating a better life for you and for others.